Vitamin D: A Potential Mitigation Tool for the Endemic Stage of the COVID-19 Pandemic? - Briceno Noriega, Daniela; Savelkoul, Huub F. J. (Frontiers in Public Health, 2022)
The impact of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic and associated development of clinical symptoms of COVID-19 have presented an enormous global impact on our health care systems, public health and economy. To date several observational epidemiological studies consistently found that vitamin D deficiency, measured as low levels of circulating 25-hydroxyvitamin D, is associated with cardiovascular diseases, diabetes, certain cancers, autoimmune diseases and many infectious diseases, including acute respiratory infections. Since vitamin D is not merely immunosuppressive but also acts as an immunomodulator in tolerance and homeostasis, many experts have considered a role of vitamin D in the prevalence and severity of immune mediated inflammatory diseases, such as SARS-CoV-2, adding to the evidence of the importance of vitamin D in the immune response against viral respiratory infections and reinforcing the need for targeted vitamin D supplementation, with a focus on high-risk populations and a high-dose supplementation treatment for COVID-19 hospitalized patients. The expected transition to endemicity of SARS-CoV-2 even further corroborates as a potential of vitamin D as an potential mitigation tool for the prevention of COVID-19. The aim of this paper is to analyse the current evidence regarding vitamin D and present a hypothesis of its potential role in the current COVID-19 pandemic and in the future as a potential preventive measurement in public health.